Softbots 4.0: Supporting Cyber-Physical Social Systems in Smart Production Management - Rabelo, Ricardo J.; Zambiasi, Saulo P.; Romero, David (International Journal of Industrial Engineering and Management, 2023)
This paper presents the results of a research work that aimed at investigating the usage of softbots – as digital intelligent software assistants – as a supporting technology to help in excelling smart production management composed of cyber-physical systems (CPS). This work also attempts to differentiate the many equivalent terms used in the literature to softbots, trying to demonstrate that all of them are just types of softbots. Softbots 4.0 acts as a smart humanmachine interface, representing a digital virtual assistant to handle human-related issues when implementing the concept of Operator 4.0. Yet, the concept of Softbot 4.0 is framed against the RAMI 4.0 model in a way to show how it can also be taken as an (intelligent) manufacturing entity. The main goal of Softbots 4.0 is to support the Operator 4.0 in interfacing with smart machines, robots, and systems, aiding people in the automatic, planned or pro-active execution of different, repetitive or complex tasks, efficiently in a more symbiotic human-machine environment. Five different cases have been selected for the assessment, implemented as software prototypes in different production management and shop floor control scenarios close to real CPS. The high potential of the softbots approach could be observed, especially when combined with other enabling technologies for Industry 4.0. A global assessment and reflections on these experiments are discussed at the end. Article history: Received (November 24, 2022); Revised (March 7, 2023); Accepted (March 8, 2023); Published online (March 13, 2023)